The Association Between Secondhand Smoke Exposure and Health Complaints at Kopi Kenangan Manado - M Fadhel Nurmidin (International Journal of Health and Pharmaceutical (IJHP), 2025)
Background: Indonesia is among the countries with the highest smoking prevalence worldwide, with significant impacts on passive smokers exposed in public spaces. Coffee shops such as Kopi Kenangan are among the locations with high potential for secondhand smoke exposure, particularly among young people. Objective: This study aimed to analyze the association between secondhand smoke exposure and health complaints among visitors of Kopi Kenangan in Manado City. Methods: A cross-sectional design was applied with 150 randomly selected respondents. Data were collected through a structured questionnaire covering respondents’ characteristics, secondhand smoke exposure, and reported health complaints. Statistical analysis was performed using the chi-square test. Results: Most respondents were aged 18–30 years (72%) and male (55.3%). The highest exposure to secondhand smoke occurred in outdoor areas (72%). The main health complaints reported were cough/throat irritation (32.1%), mild shortness of breath (21.4%), and headache (15.3%). Statistical analysis showed a significant association between secondhand smoke exposure, both outdoors and indoors, and health complaints (p<0.05). Suggestion: Strengthening the implementation of Smoke-Free Area (KTR) policies in public spaces, including coffee shops, alongside health education for the community, is essential to raise awareness of the dangers of secondhand smoke exposure.